Serum biomarkers and clinical characteristics of patients with Hodgkin lymphoma - Simonović, Olivera; Todorović, Milena; Mihaljević, Biljana; Stoimenov-Jevtović, Tatjana; Petković, Ivan; Mačukanović -Golubović, Lana; Marjanović, Goran (Vojnosanitetski pregled, 2020)
Background/Aim. In classical Hodgkin’s lymphoma (cHL) the existing prognostic scoring systems do not include markers that adequately reflect the interaction of malignant Hodgkin and Reed-Sternberg (HRS) cells and tumor environment. The aim of this study was to determine the relationship between serum Galectin-1 (Gal-1) and soluble CD163 (sCD163) and the clinical status of patients with cHL, with special emphasis on the presence of relapse, progression, or resistance to the therapy applied. Methods. The research included 79 patients of whom 63 were patients with cHL, and the control group of 16 healthy volunteers. The study group of 63 patients with cHL included a subgroup of newly diagnosed patients without therapy, newly diagnosed patients with therapy, patients with relapse and progression of the disease and primary refractory patients during 2014 and 2015. Results. Analysis of the levels of sCD163 and Gal-1 within a group of patients suffering from cHL showed that the values of both molecules were higher in relapsed patients and the subgroup with progressive disease comparing to the subgroup of newly diagnosed patients without therapy or patients with therapy onset. Conclusion. Determination of Gal-1 and sCD163 levels is simple and reliable analysis that can contribute to the identification of high-risk patients with cHL and deserves inclusion in current prognostic scoring systems.